TEACHER’S EXPERIENCES OF TEACHING GROSS MOTOR SKILL FOR CHILDREN WITH OBESITY: A PHENOMENOLOGICAL STUDY - Muchammad Arif Muchlisin (Jurnal Ilmiah Didaktika, 2020)
Improving gross motor skill in early childhood education is very important. However, few qualitative studies have investigated teachers’ experience of teaching gross motor skill with obese children. The purpose of this present study is to explore the early childhood educators’ experiences of teaching gross motor skill children with obesity from six kindergartens in the Yogyakarta district. Nine teachers participated in this study. Data were gathered through semi-structured interviews. Data also were qualitatively analyzed using the phenomenological study with the Moustakas model. Four thematic categories emerged: positive perception; flexibility; diverse role, and barriers. Teachers described the feeling when teaching gross motor for obese children, the flexibility of gross motor teaching. Teachers also expressed how the role was used for obese children and having barriers faced by teachers. Implications of these findings are discussed and recommendations are made for future research.